MORFOLOGI POLA MUKIMAN ADATI BALI - Alit, I Ketut (Jurnal Natah, 2004)
The settlement pattern of Bali tradition is a local genius which be manifested from philosophy and concept of Hindus community. Geography factor has role in developing the diversity of the pattern settlement typology. This typology is a place to ongoing settle in accordance with the idealism, social culture and society behavior.The Settlement morphology of Bali tradition is evidently a process of change, from the process leading to an adaptation till the process that totally changes from its original form. The process morphology is essentially influenced by both internal and external factors. The main issues are happening at a various level of morphology and its problem is a degradation of physic and non physic values.Nowadays, the morphology shows obviously the rapid movement from the rural tradition settlement pattern towards an urban area. Thus, it seems that we strongly require the integrated and sustainable effort to precisely understanding the issue between tradition and modernization in order to take the right and proper decision.